2022
DOI: 10.1093/pcp/pcac043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics at Early Stages of the Symbiotic Interaction Between Oryza sativa and Nostoc punctiforme Reveals Novel Proteins Involved in the Symbiotic Crosstalk

Abstract: Symbiosis between cyanobacteria and plants is considered pivotal for biological nitrogen deposition in terrestrial ecosystems. Despite extensive knowledge of the ecology of plant-cyanobacterium symbioses, little is known about the molecular mechanisms involved in recognition between partners. Here, we conducted a quantitative sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) pipeline to analyse protein changes in Oryza sativa and Nostoc punctiforme during early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…This is in line with previous work showing that symbiotic cyanobacteria, such as Nostoc , exhibit high levels of proteomic plasticity and only express a small fraction of their proteome at any given point in time 30,63,64 . This is also in agreement with the coverage of the respective endoproteomes where 65% and 20% of all proteins in Synechocystis and Nostoc , respectively, have been identified by MS-based proteomics 65,66 .…”
Section: Resultssupporting
confidence: 88%
“…This is in line with previous work showing that symbiotic cyanobacteria, such as Nostoc , exhibit high levels of proteomic plasticity and only express a small fraction of their proteome at any given point in time 30,63,64 . This is also in agreement with the coverage of the respective endoproteomes where 65% and 20% of all proteins in Synechocystis and Nostoc , respectively, have been identified by MS-based proteomics 65,66 .…”
Section: Resultssupporting
confidence: 88%
“…Two of these COG groups, T in SYMB-1 and SYMB-2 and Q in SYMB-1 and SYMB-2, stand out, as they were the only two COGs with both enriched and unique genes. COG group T corresponds to signal transduction mechanisms that may contribute to the cyanobiont’s ability to recognize the host chemical signals, which is a necessary step in the establishment of symbiosis [ 25 77 78 ]. The high number of genes found in COG group Q, which corresponded to secondary metabolism, indicated that natural products might play a more significant role in the symbiosis than previously thought, consistent with observations made on the uniqueness of metabolites in cyanobionts [ 5 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the field of molecular plant sciences, some researchers argue that evidence of a mutual exchange of chemicals or symbiogenesis of specific organs is required. However, there are examples of well defined plant–microbe symbiotic interactions that do not require the development of specific organs in the plant (Khan et al, 2012; Alvarenga and Rousk, 2022; Álvarez et al, 2022). In the same way, there is evidence of symbiotic interactions in which clear benefits to both partners cannot be ascertained and, thus, their categorization as mutualistic is debated.…”
Section: The Obstacles Accompanying the Umbrella‐term Symbiosismentioning
confidence: 99%
“…In the same way, there is evidence of symbiotic interactions in which clear benefits to both partners cannot be ascertained and, thus, their categorization as mutualistic is debated. One example is the Oryza – Nostoc association, in which the chemical exchange is not yet directly proven, despite documentation of endophytic colonization and an increase in plant yield in co‐cultivation (Álvarez et al, 2022). Hence, often neither symbiosis nor mutualism are applied to describe rice–cyanobacteria associations, resulting in a potential disregard of these interactions.…”
Section: The Obstacles Accompanying the Umbrella‐term Symbiosismentioning
confidence: 99%
See 1 more Smart Citation